EFFECTS OF GIVING DRAGON FRUIT PEEL JUICE THROUGH DRINKING WATER TO INCOME OVER FEED COST AND PERFORMANCE IN BROILER CHICKEN - C., Darmawan; Sukanata, I W.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika; Vol 11 No 3 (2023): Vol. 11 No. 3 Tahun 2023; September - December, 2023)
This study aims to know the effects of giving dragon fruit peel juice through drinking water towards the income over feed cost in broiler chicken breed that has been implemented for 5 weeks. This study used completely randomized design (CRD) that consist of 4 treatments, 4 replicates that contains 4 chicken each. The treatments that is given is (P0) that is not given any dragon fruit peels, (P1) that is given 2% of dragon fruit peel juice mixed in their drinking water, (P2) that is given 4% of dragon fruit peel juice mixed in their drinking water, and (P3) that is given 6% of dragon fruit peel juice mixed in their drinking water. The observed variables are feed consumption, water intake, final body weight, body weight gain, feed conversion ratio , income over feed cost and performance index. The results of this study showed that ration consumption and drinking water consumption were not significantly different (P>0.05) better than broiler chickens that received (P0 treatment). The final body weight of P2 and P3 treatments was significantly (P<0.05) better than the others that received P0 and P1 treatments. The increase in body weight of broiler chickens that received P1, P2, and P3 treatments was significantly better(P<0.05) higher than P0 treatment, while the FCR values ??of the three treatments were not significantly different (P>0.05). Income over feed cost was significantly different (P<0.05), where P1, P2, and P3 had a higher value than treatment P0 and the performance index experienced a significantly different increase (P<0.05). Based on the results of this study, it was concluded that giving dragon fruit peel juice 2%,4% and 6% in drinking water could not increase ration consumption, drinking water consumption, and FCR value but could increase weight gain, Income over feed cost , and performance index significantly and at the levels of 4% and 6% were able to increase the final body weight.   Keywords : Dragon fruit peel juice, broiler chicken, income over feed cost